An Importance-Performance Map to Eco-Friendly Restaurants In Indonesia’s Tourism Cities - Anisa Zahwa Akbara (Business Management Analysis Journal (BMAJ), 2026)
The growing focus on sustainability in the food service industry aligned with global environmental objectives, particularly in tourism cities where restaurants significantly impacted ecological systems. This study explored the implementation of sustainable practicesâ€”Sustainable Sourcing Ingredients (SSI), Waste Management Practices (WMP), and Energy Efficiency Measures (EEM)”in eco-friendly restaurants across Jakarta, Bandung, and Nusa Tenggara Timur (NTT), Indonesia. Using the Importance-Performance Map (IPM), the research identified key factors influencing customer perceptions of sustainability and examined how the overall customer experience moderated this relationship. Findings revealed that while SSI was a strength due to its alignment with customer values, WMP and EEM lagged in performance despite their importance. Customer Experience (CE) emerged as a critical yet underperforming factor, significantly influencing sustainability perceptions and customer loyalty. Recommendations included improving waste management strategies, enhancing energy efficiency communication, and creating memorable customer experiences to align with eco-conscious expectations. This study provided actionable insights for restaurant operators, policymakers, and stakeholders in fostering sustainable food service management while preserving tourism ecosystems in Indonesia.